Annual dynamics of benthic foraminiferal populations in the Tramandaí-Armazém Lagoon, southern Brazil (Ocean and Coastal Research, 2024)
Modern coastal environments are considered highly selective and dynamic, not only due to the natural variabilityof physical and chemical parameters, but also because of anthropogenic contamination. Our study aims to identifyenvironmental and/or anthropogenic factors influencing benthic foraminiferal abundances over a period of one yearin the Tramandaí-Armazém Lagoon, southern Brazil. Assemblages were composed exclusively of agglutinated speciesassigned to the genera Trochammina, Trochamminita, Ammotium, Haplophragmoides and Miliammina. Total abundancesvaried throughout the year, reaching the highest values during the wetter months of March and July, when living anddead assemblages became dominated by Ammotium salsum. This pattern is likely related to salinity fluctuations dueto changes in freshwater input that, consequently, affected the amount of organic matter (e.g., phytodetritus) broughtinto the lagoon by surrounding drainages. To assess the impact of anthropogenic pollution, we evaluated total relativeabundances of deformed tests in the Tramandaí-Armazém Lagoon. Relative abundances of deformed tests were thehighest during the months of January and March, when contaminant (e.g., sewage) discharge was probably increaseddue to the seasonal population growth in the region.